2021
DOI: 10.1002/jnr.24835
|View full text |Cite
|
Sign up to set email alerts
|

Larger bilateral amygdalar volumes are associated with affective loss experiences

Abstract: Affective loss (AL) (i.e., bereavement, relationship breakup) is a stressful life event leading to a heightened risk of developing a psychiatric disorder, for example, depression and anxiety disorder. These disorders have been associated with altered subcortical brain volumes. Little is known though, how AL in healthy subjects is linked to subcortical volumes. In a study with 196 healthy young adults, we probed the association between AL across the individual entire life span, assessed via the List of Threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Based on animal studies, it is thought that the hippocampus is sensitive to stress and that the hippocampus mediates the stress response and release of glucocorticoids from the hypothalamic-pituitary-adrenal (HPA) axis (McEwen & Sapolsky, 1995). Chronic activation of the HPA axis due to stress or anxiety (Juruena et al, 2020) may lead to volume loss in the hippocampus, which has been demonstrated in studies assessing stressful events (Acosta et al, 2021;Papagni et al, 2011) and post-traumatic stress disorder (Ahmed-Leitao et al, 2016;Kitayama et al, 2005;Sapolsky et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Based on animal studies, it is thought that the hippocampus is sensitive to stress and that the hippocampus mediates the stress response and release of glucocorticoids from the hypothalamic-pituitary-adrenal (HPA) axis (McEwen & Sapolsky, 1995). Chronic activation of the HPA axis due to stress or anxiety (Juruena et al, 2020) may lead to volume loss in the hippocampus, which has been demonstrated in studies assessing stressful events (Acosta et al, 2021;Papagni et al, 2011) and post-traumatic stress disorder (Ahmed-Leitao et al, 2016;Kitayama et al, 2005;Sapolsky et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the reports substantively and performed statistical analyses using percentage values from the volBrain procedure. In this study, we focused on the uncorrected volumes of the left and right caudate nucleus, the total volume of the caudate nucleus, and brain tissue [37].…”
Section: Imaging Analysismentioning
confidence: 99%
“…However, when these romantic relationships go through “heartbreak” or “post-relationship grief”, universal life stress occurs that affects the microbiota. Other research highlights that poor-quality affective-sexual relationships can lead to depression [ 42 ], anxiety [ 43 ], fear [ 44 ], anguish [ 45 ], memory disturbances [ 46 ], emotional disorders [ 47 ], environmentally-sensitive physiological impairment (e.g., of central nervous, endocrine, and immune systems) [ 48 ], different somatic symptoms [ 49 ], and even an increase in the tendency to commit suicide in some people [ 50 ]. In addition, there is increased dissatisfaction with the relationship [ 51 ].…”
Section: Introductionmentioning
confidence: 99%